การสูญหายของโปรตีนพี 16 กับระยะเวลาการมีชีวิตในผู้ป่วยมะเร็งตับชนิดเฮปปาโตเซลล์ลูล่าคาร์ซิโนม่า - จตุรงค์ ตันติมงคลสุข (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
Objective: For comparative study between survival time and loss of p16 protein expression in the hepatocellular carcinoma patients. Methods: The samples were selected from hepatocellular carcinoma patients who were diagnosed with liver biopsy in Chulalongkorn Hospital. The patients were classified in two groups, normal p16 protein expression and loss of p16 protein expression, by immunohistochemistry method for p16 protein detection. The sample sizes required at least twenty patients in each groups. The clinical data, such as risk factors for hepatocellular carcinoma, staging, laboratory chemistry, method of treatment and survival time, was collected and analyzed for difference detection. Results: The fifty-five specimens were stained by p16 protein immunhistochemistry method. There were 16 specimens (26.1%) which loss of p16 protein expression. When clinical data was analyzed, there was no any significant difference in these factors except history of alcoholic drinking. The median survival time was 14.1 weeks (95%Cl8.29-21.13) in the patients with positive p16 protein staining and 9.6 weeks (95%Cl 9.15-9.99) in the patients with negative p16 protein staining but there was no significant statistical difference. Summary: There was no different in survival times between normal and loss of p16 protein expression in hepatocellular carcinoma. The prevalence of loss of p16 protein expression in Thai hepatocellular carcinoma patients was 29.1 percent